The Mechanism of Suppression By a Protective Peptide in a Mouse Model of Multiple Sclerosis - (:unkn) unknown (My University, 2015)
Multiple Sclerosis (MS) is an autoimmune demyelinating disease of the central nervous system (CNS). MS is characterized by an immune response directed against myelin sheath. This immune response results in demyelination, which leads to the clinical symptoms of MS. It is accepted that MS is mediated by T helper 1/ T helper 17 immune responses. However, the role of B cells and antibodies (Abs) are still under debate. The primary animal model for MS is the experimental autoimmune encephalomyelitis (EAE) that is induced by immunizing animals with one of the myelin components. We previously showed that immunizing mice with the recombinant form of myelin oligodendrocyte glycoprotein (rMOG) results in ameliorated EAE compared to mice immunized with the encephalitogenic peptide MOG35-55. This amelioration was due to the presence of a cryptic epitope of MOG61-85 in rMOG as observed in previous peptide mapping analysis. We further investigated the mechanism of EAE amelioration in mice immunized with a longer peptide MOG35-85, encompassing both MOG35-55 and MOG61-85 peptides. The mechanism of suppression was shown to be independent of interleukin-10 (IL-10) secretin. This led to the hypothesis that MOG61-85 ameliorates EAE through the secretion of transforming growth factor-beta (TGF-β). Therefore, B cell deficient (B cell-/-) mice were either co-immunized with both MOG35-55 and MOG61-85 peptides or immunized with MOG35-55 only. Mice were monitored for EAE induction and progression. The cellular response to MOG61-85 in vitro priming was assessed using flow cytometry. Results showed comparable FoxP3 expression level in CD4+CD25+ T cells between cell cultures; however a slight increase in FoxP3 expression in CD8+CD25- T cell population was observed with MOG61-85 in vitro priming that was dependent on MOG61-85 in vivo priming. These results support the suppressive effect of MOG61-85 on the immune response and suggest a role of CD8 T regulatory (Treg) cell population in EAE amelioration. Evaluation of MOG61-85 specific signaling cytokine showed that MOG61-85 induces regulation independent of IL-10 secretion. This was confirmed by immunizing wild-type (WT) and IL-10 deficient (IL-10-/-) mice with rMOG and measuring the anti-inflammatory cytokines produced in response to MOG61-85 in vitro priming. Analysis for TGF-β showed that MOG61-85 specific immune response is characterized by high TGF-β secretion. To evaluate the immune response generated with MOG61-85 stimulation, TGF-β:IL-6 ratio was mathematically calculated. Data showed that MOG61-85 induces an anti-inflammatory immune response characterized by high TGF-β and low IL-6 secretions. These experiments provide understanding of the protective immune response generated in response to MOG61-85 priming.
Keywords: Autoimmunity; Demyelination; Experimental Autoimmune Encephalomyelitis; Immune Regulation; Inflammation; Multiple Sclerosis